CODING WITH MYTHICAL CREATURES - Burns, Kylie; Eason, Sarah; Leaf, Christina; Smith, Eric (Minneapolis, MN : Bellwether Media, Inc., 2024)
"Information accompanies instructions for various mythical-creature-themed activities that demonstrate skills needed for coding. The text level and subject matter are intended for students in grades 3 through 8"-- Provided by publisher.
Includes index
Bibliography: page 23
Ages 7-13
Grades 4-6
Keywords: Computer programming -- Juvenile literature; Animals, Mythical -- Juvenile literature